ENVIROMENTAL FACTORS AS CORRELATES OF ACADEMIC PERFORMANCE AMONG INTERNALLY DISPLACED PUPILS IN NORTH CENTRAL, NIGERIA - BISSALLAH , EKELE COMFORT (Sokoto Educational Review, 2025)
This study examined the impact of environmental factors on the academic performance of primary school pupils in Internally Displaced Persons (IDP) camps in North Central Nigeria. Utilizing a descriptive correlational survey design, the study involved 3,608 pupils from IDP camps across Abuja, Benue, Kogi, Kwara, Nasarawa, Niger, and Plateau states, with a sample size of 719 determined using Research Advisor (2006). Multistage, stratified, and simple random sampling techniques were employed to select the camps, schools, and pupils. Data were collected using the Environmental Factor Checklist (EFC) and the Pupils Performance Test (PPT), both validated with reliability indices of 0.71 and 0.72, respectively. Analysis using percentages and Pearson Product Moment Correlation (PPMC) revealed that inadequate infrastructure, poor water supply, insufficient sanitation, and substandard classroom facilities negatively affected academic performance. The study recommends that local voluntary organizations and government agencies collaborate to address these challenges by improving access to clean water, upgrading sanitation facilities, and ensuring safe and well-equipped learning environments to enhance the overall well-being and academic performance of pupils in IDP camps.